Respiratory Syndrome Coronavirus Infections: Possible Mechanisms of Neurological Implications—A Systematic Review - de Assis, Gilmara Gomes; Murawska-Cialowicz, Eugenia; Cieszczyk, Pawel; Gasanov, Eugene V. (Frontiers in Neurology, 2020)
Within the context of the worst pandemic of the century—Covid-19—which emerged in China and has spread across the entire globe over the last 6 months, increased knowledge about viral behavior that be prognostic is crucial. Following the patterns of other coronaviruses (CoVs), particularly those infecting the respiratory tract, neurological manifestations have been reported in patients with Covid-19. Such manifestations highlight the neurovirulence of this severe acute respiratory syndrome (SARS)-CoV2. In order to collect all available information on the implications and mechanisms of infections by respiratory CoVs, a systematic review was designed following the PRISMA protocol. The following PICO strategy (patient, problem, or population; intervention; comparison, control, or comparator; outcomes) was adopted: P included healthy individuals, patients, and animal models susceptible to human-specific viruses; I included molecular, cell culture, and comparative experimental studies; C included healthy, diseased, and immunized conditions; and O represented the virulence and pathogenicity of respiratory CoVs and their effects on the central nervous system (CNS). Searches were conducted in PubMed databases from March 30 to April 1, 2020. Results indicate the involvement of the CNS in infections with various CoVs. Infection typically begins in the airway epithelia with subsequent alveolar involvement, and the virus then spreads to the CNS via neuronal contacts with the recruitment of axonal transport. Neuronal infection and regulated cell death are the main factors causing a generalized encephalitis.